Erosion and its Implication on Hydrocarbon Generation in ‘ARD’ Block, Akimeugah Basin,West Papua - Sugeng Sapto Surjono; Yohanes Ardhito Triyogo Varianto; Salahuddin Salahuddin (Journal of Applied Geology, 2020)
Akimeugah Basin in the western part of Aru Trough is included as a Paleozoic Basin which is one of the potential hydrocarbon-producing basins in Eastern Indonesia. Tectonic evolution in Akimeugah Basin during Cambrian to present has produced a very significant erosion that affected the hydrocarbon generation process. ‘ARD’ Block study uses three exploratory well data including well report and 26 lines of 2D seismic data with a total length of 5,812.55 kilometers and the distance between seismic lines ranging from 10 to 15 kilometers. Seismic data is processed with IHS Kingdom software for tectonostratigraphy analysis, while calculation and erosion analysis are performed by combining well data consisting of sonic, vitrinite reflectance and seismic. To get a burial history model and generation & expulsion period, this study utilizes Petromod software. Five phases of the tectonic evolution led to four times of erosional period with a sediment thickness of 290 – 3,370 feet were loss. The erosion of the sedimentary rocks causes the maturation process delayed more than 200 million years. Burial history in the study area with the erosion absence assumption results a hydrocarbon generation starting from around 210 million years ago. Meanwhile, by considering the loss of eroded sedimentary rocks during four tectonic phases, hydrocarbon generation time just occurred 3.1 million years ago.